2021
DOI: 10.1161/hypertensionaha.120.12858
|View full text |Cite|
|
Sign up to set email alerts
|

Starting Antihypertensive Drug Treatment With Combination Therapy

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Till now, one point of discussion was that none of the trials of SPCs had a cardiovascular end point. 22 The results of our study strongly support the recommendations of national and international guidelines to treat arterial hypertension with a combination therapy given in 1 single pill whenever possible. 23 Implementation of the given clinical evidence regarding SPC into daily practice seems to be a challenge.…”
Section: Discussionsupporting
confidence: 83%
“…Till now, one point of discussion was that none of the trials of SPCs had a cardiovascular end point. 22 The results of our study strongly support the recommendations of national and international guidelines to treat arterial hypertension with a combination therapy given in 1 single pill whenever possible. 23 Implementation of the given clinical evidence regarding SPC into daily practice seems to be a challenge.…”
Section: Discussionsupporting
confidence: 83%
“…Sebagian besar sumber informasi penggunaan SPC berasal dari studi observasional dengan desain retrospektif jangka pendek. 21 KEAMANAN Salah satu tujuan penggunaan SPC adalah meminimalisir efek samping obat karena dosis tinggi pada monoterapi. Penggunaan SPC dapat mengurangi dosis obat individual dengan mengombinasikannya dengan obat lainnya.…”
Section: Luaran Kardiovaskularunclassified
“…Africa has the highest prevalence of hypertension in the world as 46% of adults aged 25 years and above have a raised blood pressure (2,4), and a study in Southern Nigeria found a prevalence of 40.8% (5). The primary goal of antihypertensive therapy is to prevent morbidity and mortality associated with hypertension (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%